Think, care, act : teaching for a peaceful future - Cannon, Susan Gelber (Peace education., 2011)
Committed to teaching for peace and justice, the author brings to life a teaching approach that empowers youth: * to think critically and creatively about historical, current, and future issues, * to care about classmates and neighbors as well as the global community, * to act--locally and globally--for the greater good. Think, Care, Act: Teaching for a Peaceful Future is readable, practical, conversational, and intimate. It will inspire readers to build a just and peaceful world. Think, Care, Act depicts the daily successes and struggles a peace educator undergoes in encouraging students to envision peace and gain tools to build a culture of peace. The author uses three imperatives--think, care, act--to infuse required curricula with peace, character, and multicultural concepts in daily activities throughout the year. Chapters address critical and creative thinking; media and political literacy; compassionate classroom and school climate; explorations of racism, gender issues, civil discourse, global citizenship, war, and peace; and school, community, and global social-action projects. Chapters include rationales, lesson expectations, and classroom "play-by-play." Students' feedback about the impact of lessons is also featured. With its combination of theory and practice Think, Care, Act is unique. It will motivate teachers, education students, and scholars to employ "think, care, act" frameworks to empower students to build a peaceful future.